An optimal model for predicting the productivity of perforated vertical HTHP wells. (10th February 2014) - Hu, Jiancheng; Xu, Jiuping; Wang, Shize; Qi, Bin; Qiao, Zhiguo
Abstract As perforation helps regulate inflow from the reservoir, the optimisation of the perforating parameters is critically important in increasing productivity. In this paper, a one‐dimensional reservoir/wellbore coupling model is presented to predict the productivity of perforated vertical high‐temperature‐high‐pressure (HTHP) wells. A comprehensive perforation skin factor is developed in the model, which takes into consideration many reservoir and perforation parameters, such as length, density, radius, anisotropy, phasing, partial penetration, perforation damage and formation damage. An optimisation strategy is established to investigate the effect of the perforation parameters on productivity based on the skin factor of a well. The model is applied to a 7100 m deep HTHP gas well to demonstrate its use in determining optimal perforation parameters. The simulation results demonstrate that an optimisation strategy improves the perforated well inflow performance. Then, a sensitivity analysis is conducted to investigate the effect of reservoir and perforation parameters on productivity.